2015
DOI: 10.1126/scitranslmed.aaa3636
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in silico: Individual-specific mathematical models and virtual clinical populations

Abstract: Trauma-induced critical illness is driven by acute inflammation, and elevated systemic interleukin-6 (IL-6) after trauma is a biomarker of adverse outcomes. We constructed a multicompartment, ordinary differential equation model that represents a virtual trauma patient. Individual-specific variants of this model reproduced both systemic inflammation and outcomes of 33 blunt trauma survivors, from which a cohort of 10,000 virtual trauma patients was generated. Model-predicted length of stay in the intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 79 publications
1
68
0
Order By: Relevance
“…Over a decade of studies in cells, mice, large animals, and humans, we have developed an integrated view of the postinjury acute inflammatory response, which is regulated by initial chemokine-driven cues and propagated by DAMPs. These studies involved multiple paradigms of acute inflammation, including endotoxemia and experimental sepsis in mice (32,35,109,125), rats (39,107,112), and swine (43,50,112,116)), experimental trauma/ hemorrhagic shock in mice (35,45,81,84,97,125), and traumatic injury in humans (3,31,84,110,136,158).…”
Section: The Conundrum Of Acute Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a decade of studies in cells, mice, large animals, and humans, we have developed an integrated view of the postinjury acute inflammatory response, which is regulated by initial chemokine-driven cues and propagated by DAMPs. These studies involved multiple paradigms of acute inflammation, including endotoxemia and experimental sepsis in mice (32,35,109,125), rats (39,107,112), and swine (43,50,112,116)), experimental trauma/ hemorrhagic shock in mice (35,45,81,84,97,125), and traumatic injury in humans (3,31,84,110,136,158).…”
Section: The Conundrum Of Acute Inflammationmentioning
confidence: 99%
“…As an adjunct to translational research in the setting of trauma, sepsis, and related inflammatory processes, we have suggested the concept of Translational Systems Biology (7,8,11,145,150,151). This concept encompasses the use of computational simulations of clinical trials (4,36,79,147), computational models of individuals to drive personalized medicine (31,84,116,136), streamlined usage of experimental murine animal models (146), and rational device design (106). The cornerstone of Translational Systems Biology is computational modeling (1,7,9,98,143,149,151), which could allow for overcoming translational challenges inherent to complex diseases.…”
Section: Translational Systems Biology Of Inflammationmentioning
confidence: 99%
“…Virtual populations have been used by others, particularly in the field of quantitative systems pharmacology (16,(22)(23)(24)(25)(26)(27)(28)(29)(30). Overwhelmingly (see, for instance, refs.…”
mentioning
confidence: 99%
“…These virtual population methods require dozens to thousands of samples to create virtual populations that are representative of the target population (23,26,(28)(29)(30). On the other hand, the VEPART procedure proposed herein works with very small amounts of data, and "expands" the available data in an effort to model the heterogeneity expected in the full population.…”
mentioning
confidence: 99%
“…We utilize an HPC implementation of a previously developed system/population-level validated 37 ABM of the innate immune response [6] (the Innate Immune Response ABM or IIRABM) to generate a 38 first approximation behavioral landscape of sepsis to guide the development of suitable metrics with 39 which to characterize that behavioral landscape. Though developed over 15 years ago, the IIRABM 40 remains valid insomuch it reproduces the overall dynamics of the acute inflammatory response, 41 producing recognizable system level outcomes (healing, pro-inflammatory death, hypo-immune death and 42 overwhelming initial infection) using a knowledge-based rule system that, while admittedly incomplete, 43 has not been demonstrated to be incorrect in its represented behaviors by accumulated discoveries since 44 its development. In fact, some of the behaviors generated by the IIRABM presaged their general 45 recognition within the sepsis community, specifically the temporal concurrence of pro-and 46 anti-inflammatory cytokine responses (as opposed to sequential pro-and compensatory responses) [7,8] 47 and the importance of the immuno-incompetent/attenuated recovery phase of sepsis, particularly with characterization of the behavioral landscape of the IIRABM represents a lower bound, first 53 approximation of the ability to characterize the real world system.…”
mentioning
confidence: 99%